Is the Anthropomorphic Virtual Anchor Its Optimal Form? An Exploration of the Impact of Virtual Anchors’ Appearance on Consumers’ Emotions and Purchase Intention - Shizhen Bai; Luwen Cao; Jiamin Zhou (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
In recent years, virtual anchors have become vital in live marketing due to their anthropomorphic features and interactive advantages. However, are anthropomorphic virtual anchors the best option? This study employs neuromarketing tools to examine the impact of virtual anchor appearance on consumer purchase intention, investigating the mediating role of emotional response and the moderating role of product type. The findings reveal the following: (1) the anthropomorphism level of virtual anchors is significantly positively correlated with purchase intention; (2) anthropomorphism exhibits a positive U-shaped relationship with emotional response, while inhuman images rapidly trigger emotional arousal, but this does not directly translate into purchase behavior; (3) for hedonic products, high anthropomorphism significantly increases purchase intention, whereas utilitarian products are more likely to be purchased when anthropomorphism is low. These findings provide a theoretical foundation for virtual anchor design, address the empirical gap regarding the interaction between anthropomorphism and product type, and offer scientific guidance for digital marketing strategies.